Implementation of Authentic Learning on Problem-Solving Skills: A Review of the Effectiveness of the Kurikulum Merdeka Teaching Module - Alfi Yunita Angelina; Mustika Wati; Surya Haryandi (Universitas Lambung Mangkurat, 2026)
One crucial 21st-century competency is problem-solving. Based on the results of the 2022 PISA, Indonesia's mathematics, literacy, and science skills remain low. These skills are the foundation of students' problem-solving skills. This finding is also based on a baseline test conducted at a school in Tanah Laut Regency, which showed that students' problem-solving skills were still low and there was a lack of teaching modules that practiced these skills. Therefore, this study aims to describe a review of the effectiveness of the authentic learning teaching module of the Kurikulum Merdeka on problem-solving skills. This study applies the R&D research type using the ADDIE model. A total of 48 students participated in the trial, comprising 24 students from Class XI C and 24 students from Class XI D at a public high school in Tanah Laut Regency. The data were collected through a learning achievement test. The analysis used an independent sample t-test, complemented by an effect size calculation. Based on the data calculation, the effect size was 1.85, which is categorized as high. This indicates that the developed module is highly effective in training students' problem-solving skills and students’ learning performance. Thus, it can be concluded that the authentic learning teaching module of the Kurikulum Merdeka is effective for training problem-solving skills. The implication of this study is that the application of authentic learning through teaching modules can be an alternative support for physics learning to train students' problem-solving skills.